"There's a Pain App for That". Issue 6 (June 2015) - Lalloo, Chitra; Jibb, Lindsay A.; Rivera, Jordan; Agarwal, Arnav; Stinson, Jennifer N.
<x xml:space="preserve">Abstract</x> Objectives: There are a growing number of pain self-management applications (apps) available for users to download on personal smartphones. The purpose of this study was to critically appraise the content and self-management functionality of currently available pain apps. Methods: An electronic search was conducted between May and June 2014 of the official stores for the 4 major operating systems. Two authors independently identified patient-focused apps with a stated goal of pain management. Discrepancies regarding selection were resolved through discussion with a third party. Metadata from all included apps were abstracted into a standard form. The content and functionality of each app as it pertained to pain self-management was rated. Results: A total of 279 apps met the inclusion criteria. Pain self-care skill support was the most common self-management function (77.4%). Apps also purported providing patients with the ability to engage in pain education (45.9%), self-monitoring (19%), social support (3.6%), and goal-setting (0.72%). No apps were comprehensive in terms of pain self-management, with the majority of apps including only a single self-management function (58.5%). In addition, only 8.2% of apps included a health care professional in their development, not a single app provided a theoretical rationale, and only 1 app underwent scientific evaluation. Discussion: Currently available pain self-management apps for patients are simplistic, lack the involvement of health care professionals in their development, and have not been rigorously tested for effectiveness on pain-related health outcomes. There is a need to develop and test theoretically and evidence-based apps to better support patients with accessible pain care self-management.